2014
DOI: 10.1371/journal.pone.0094271
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Patterns of Liver Toxicity in Patients on Antiretroviral and Anti-Tuberculosis Drugs: A Prospective Four Arm Observational Study in Ethiopian Patients

Abstract: ObjectivesTo evaluate the incidence, type, severity and predictors of antiretroviral and/or anti-tuberculosis drugs induced liver injury (DILI).MethodsA total of 1,060 treatment naive patients were prospectively enrolled into four treatment groups: HIV patients receiving efavirenz based HAART alone (Arm-1); TB-HIV co-infected patients with CD4≤200 cells/μL, receiving concomitant rifampicin based anti-TB and efavirenz based HAART (Arm-2); TB-HIV co-infected patients with CD4>200 cells/μL, receiving anti-TB alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
64
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 37 publications
11
64
1
Order By: Relevance
“…The study participants for the present GWAS were included from a recent observational, prospective cohort study where the incidence and patterns of ARV drugs and/or ATDinduced liver toxicities were investigated (Yimer et al, 2014). In brief, newly diagnosed treatment naïve patients enrolled into the following study arms were considered for the present study:…”
Section: Study Participantsmentioning
confidence: 99%
See 3 more Smart Citations
“…The study participants for the present GWAS were included from a recent observational, prospective cohort study where the incidence and patterns of ARV drugs and/or ATDinduced liver toxicities were investigated (Yimer et al, 2014). In brief, newly diagnosed treatment naïve patients enrolled into the following study arms were considered for the present study:…”
Section: Study Participantsmentioning
confidence: 99%
“…All patients received treatment according to the national and the WHO treatment guidelines for HIV and TB as previously described (Yimer et al, 2014). In brief, all HIV patients received ARV drugs containing efavirenz and lamivudine with stavudine, zidovudine, or tenofovir.…”
Section: Drug Treatment and Patient Follow-upmentioning
confidence: 99%
See 2 more Smart Citations
“…Exploring risk factors for late diagnosis in 191 co-infected patients, Rossato, et al (2) found that extrapulmonary TB and smear-negative TB contributed significantly to this delay.…”
mentioning
confidence: 99%